Rancang Bangun Sistem Informasi Penggajian Karyawan Menggunakan Bahasa Pemograman PHP dan MYSQL - Cecep Juliansyah Abbas; Tantri Damayanti (JEJARING : Jurnal Teknologi dan Manajemen Informatika, 2019)
This study will develop a payroll information system that will be made for Manis Lor Kuningan gas station. Employee payroll system is a tool in calculating, storing and managing company data making it easier to calculate expenses. Currently Lor Lor SPBU for employee payroll still uses paper media as well as Microsoft Exel so that the repaired data can be deleted, also less effective and efficient. So the principle of efficiency is needed as an effort to support safety facilities  in  the  SPBU  business  environment for  the  process  of  managing  reports  that  can  utilize  computerized technology, then a payroll system is created using php as a programming language and mysql as a data storage or database. With the existence of a computerized payroll system that is expected to help overcome payroll problems and reduce the time to find the data needed. Keywords: payroll system, php and Mysql.